2005
DOI: 10.1051/0004-6361:20047123
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the transverse velocity of the lensing galaxy in Q2237+0305 from the lack of strong microlensing variability

Abstract: Abstract. We present a method for the determination of upper limits on the transverse velocity of the lensing galaxy in the quadruple quasar system Q2237+0305, based on the lack of strong microlensing signatures in the quasar lightcurves. The limits we derive here are based on four months of high quality monitoring data, by comparing the low amplitudes of the lightcurves of the four components with extensive numerical simulations. We make use of the absence of strong variability of the components (especially c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 32 publications
(41 reference statements)
2
30
0
Order By: Relevance
“…The same effect, but not as strong, is seen in the C-A image, again suggesting a slight demagnification of C, a magnification of A or a combination of the two. In previous microlensing studies, component D has not been seen to have as strong a microlensing signal as A and C have ( Irwin et al 1989;Alcalde et al 2002;Gil-Merino et al 2005) so therefore it is perhaps more likely that we are seeing the magnification of image A.…”
Section: Q2237+030mentioning
confidence: 84%
“…The same effect, but not as strong, is seen in the C-A image, again suggesting a slight demagnification of C, a magnification of A or a combination of the two. In previous microlensing studies, component D has not been seen to have as strong a microlensing signal as A and C have ( Irwin et al 1989;Alcalde et al 2002;Gil-Merino et al 2005) so therefore it is perhaps more likely that we are seeing the magnification of image A.…”
Section: Q2237+030mentioning
confidence: 84%
“…Assuming that the peculiar velocities of the source and lens, in their own planes, are of the same order, the last term can be neglected as well. With these approximations, the effective source velocity is reduced to the expression In the case of lensed system Q2237+0305, several studies found the transverse velocity of the lens to be in the range between approximately 500 and 2000 km s −1 (Wyithe, Webster & Turner ; Kochanek ; Gil‐Merino et al ). We adopted three values in this range and calculated the corresponding effective source velocity and rise times of HMEs.…”
Section: Resultsmentioning
confidence: 99%
“…The microlensing activity during our observations was not as important as during the periods studied by Kochanek (2004) and Anguita et al (2008). Furthermore, Anguita et al (2008) considered a shorter observation period, and used the velocity prior of Gil-Merino et al (2005), which is more constraining towards high velocities (hence favoring smaller source sizes) than the one we considered in the present study. This explains, why our derivedR s is slightly larger.…”
Section: +019mentioning
confidence: 99%
“…Previous studies have considered various priors (e.g. Kochanek 2004;Gil-Merino et al 2005). Some are more restrictive than others, but most of them have in common that they favor transverse velocities of ∼600 km s −1 in the lens plane, which correspond to projected transverse velocities of ∼6000 km s −1 in the source plane of QSO 2237+0305 (Kayser et al 1986).…”
Section: Bayesian Analysismentioning
confidence: 99%